Association between hemoglobin level and cognitive profile in old adults: A cross‐sectional survey. (30th August 2022) - Yang, Yaqi; Liu, Shuai; Gan, Jinghuan; Zhu, Han; Du, Xiaoshan; Chen, Zhichao; Ma, Lingyun; Meng, Qingbo; Yang, Fan; Chen, Hui; Ji, Yong
Abstract: Objective: In the present study, the association between Hemoglobin (HGB) level and cognitive profile was investigated and whether it affected the dementia risk in older adults. Methods: A cross‐sectional population‐based survey that included 3519 individuals ≥65 years of age was conducted in 2019. Basic demographic characteristics were collected. The neuropsychological assessments and blood tests were administered to evaluate cognition and HGB level. Generalized additive models were used to analyze the non‐linear association between HGB levels and cognitive function. Logistics regression models were utilized to analyze the associations between HGB level and dementia risk. Results: Overall, 459 (12.7%) participants were diagnosed with dementia and there were more females (54.7%) than males (45.3%). The number of subjects with anemia (3%) or hyperhemoglobinemia (5.2%) was higher than participants with normal HGB level. A visual representation of the relationship between HGB level and Mini‐Mental State Examination (MMSE) score showed an inverted U‐curve, which is more evident in female. Logistics regression models showed that anemia (odds ratio, OR = 1.826, 95% confidence interval, CI: 1.166–2.860, p  < 0.01), but not hyperhemoglobinemia, significantly increased the risk of dementia. These trends were not the same for males and females. An abnormal HGB level had greater effects in females, resulting in higher risk of dementia for females with anemia or hyperhemoglobinemia than subjects with normal HGB level including males. Conclusion: Both low and high HGB levels can lead to cognitive decline in the incidence of dementia, indicating an inverted U‐shaped curve association may exist between HGB level and global cognitive profile. Key points: An inverted U‐shaped curve association may exist between Hemoglobin (HGB) level and global cognitive profile. High hemoglobin levels within the normal range may improve the cognitive function in the elderly. Both low and high HGB levels were shown to independently increase the risk of dementia in later life. An abnormal HGB level had greater effects in females, resulting in higher risk of dementia for females with anemia or hyperhemoglobinemia than males.